The Tradition of Surah Al-Hashr Recitation As A Student’s Self-Protective Method at Sulaimaniyyah Islamic Boarding School Turkey, Indonesia - Maksalmina, Nila Munana; Atabik, Ahmad (Program Studi Ilmu Al-Qur`an dan Tafsir, Fakultas Ushuluddin, UIN Sunan Kudus, 2023)
This study examines the tradition of reciting verses 22-24 of Surah al-Hashr, a practice commonly performed within the dhikr following the compulsory Maghrib and Fajr prayers at the Sulaimaniyyah Tahfiz Islamic Boarding School in Pati. In this Islamic institution, all students are mandated to participate in this tradition, ensuring their habitual engagement in their daily lives. Employing a Living Qur'an study and a phenomenological approach, the research methodology relied on observation, interviews, and documentation within an interpretative study aimed at elaborating various human experiences. Additionally, Karl Mannheim's theory was employed to analyze the issue from objective, expressive, and documentary perspectives. This study provides the following conclusions: First, the tradition of Surah al-Hashr verses 22-24 recitation, performed on a daily basis after the compulsory Magrib and Fajr prayers, serves as a motivational tool to inspire readers and to tap into the numerous benefits it contains. Second, the objective meaning of reciting these verses establishes the long-standing nature of this tradition, with the holistic purpose of nurturing students into virtuous and Qur'anic individuals. Whereas, the expressive meaning may offer a self-protection, serving as a formidable shield against external malevolence, particularly for the students, protecting them from evil forces that seek to beguile and interfere human beings. Furthermore, it facilitates the students in their Quran memorization processes. In terms of documentary meaning, this tradition helps fostering religious devotion among students, both to their relationship with Allah (hablun minallah) and their relationship with fellow human beings (hablun minannas).